The Impact of Store Atmosphere and Product on Purchase Decisions at Coffee Aliong Sungai Duri - Muhammad Irfani; Ananda Archie (Electronic Journal of Education, Social Economics and Technology, 2026)
This study aims to analyze the effect of store atmosphere and product on purchase decisions at Coffee Aliong in Sungai Duri. The study employs a quantitative approach with an associative design. The sampling technique used is purposive sampling. The number of respondents consists of 150 consumers who met the criteria of purposive sampling. Data analysis was conducted using multiple linear regression analysis with the assistance of SPSS version 25 software, supported by validity tests, reliability tests, and classical assumption tests. The results show that partially, store atmosphere has a positive and significant effect on purchase decisions (β = 0.409; p 0.001), and product also has a positive and significant effect on purchase decisions (β = 0.312; p 0.001). Simultaneously, store atmosphere and product have a significant effect on purchase decisions (p 0.001), with a coefficient of determination (R²) of 0.427. These findings indicate that store atmosphere and product are able to explain 42.7% of the variation in consumer purchase decisions, while the remaining portion is influenced by other factors outside the research model. Practically, the results of this study emphasize the importance of managing a comfortable and consistent store atmosphere, as well as providing high quality and varied products, as the main strategies to enhance consumer purchase decisions in local coffee shops.